HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG MANFAAT MENGKONSUMSI ZAT BESI DI DESA GARINGGING TAHUN 2019 - Rismawaty Sembiring (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
Maternal Mortality Rate (MMR) about the number of maternal deaths associated with pregnancy, childbirth, and childbirth. Based on data from WHO in 2017, 500,000 people die annually during pregnancy and childbirth. Based on data from the Indonesian health demographic survey (IDHS) in 2017 about maternal mortality reached 359 per 100,000 live births and the infant mortality rate of 32 IMB per 1000 live births is according to the target in the Millennium Development Goals (MDGs) of 102 in 2015. One is still high AKI in Indonesia tends to be by anemia. The purpose of this study was to study the Relationship between Knowledge and Attitudes of Pregnant Women Regarding the Benefits of Consuming Iron in Garingging Village in 2019. Anemia is a condition where there are hemoglobin levels, hematocrit and the amount of erythrocytes entered as normal values. In people with anemia, more often called lack of blood, levels of red blood cells (hemoglobin) are below normal values. The reason, because of nutrients, acids, folic acid and vitamin B12. What often happens is anemia due to iron deficiency. The population in this study were 30 pregnant women who were sampled to meet the inclusion and exclusion criteria. And the research results obtained p = 0,000 there is a relationship between knowledge and attitudes of pregnant women about the benefits of consuming iron tablets. Keywords: Pregnant Women, Anemia, Knowledge, Attitudes